Clinical Manifestations and Prognosis of Chronic Kidney Disease after Hematopoietic Stem Cell Transplantation - Yu Zhang; Guisheng Ren; Wencui Chen; Jinzhou Guo; Xiaomei Wu; Weiwei Xu; Xianghua Huang (Kidney Diseases)
Introduction: Kidney disease is a common complication of hematopoietic stem cell transplantation (HSCT). However, there is limited research on the clinical pathology and prognosis of patients who develop chronic kidney disease (CKD) after HSCT. Methods: A retrospective analysis was conducted on 50 patients diagnosed with CKD through kidney biopsy between September 2008 and May 2024. The patients were categorized based on their pathological presentations into groups with thrombotic microangiopathy (TMA) or membranous nephropathy (MN). Results: The renal pathological results revealed that TMA was the most prevalent pathological type, accounting for 40% of cases, followed by MN at 32%, and mesangial proliferative glomerulonephritis at 16%, among others. Clinically, patients with TMA predominantly presented with renal insufficiency, whereas those with MN mainly exhibited nephrotic syndrome. Patients with MN showed favorable responses to treatment, achieving complete and partial response rates of 14.3% and 71.4%, respectively. Among the 50-patient cohort, 45 remained alive, corresponding to a 5-year overall survival rate of 87.8%. The 5-year renal survival rate was observed to be 78.8%, with 3 patients (6.98%) requiring kidney replacement therapy. Conclusion: TMA and MN are the two most common pathological findings in patients with CKD following HSCT. Both conditions exhibit favorable responses to combined steroids and immunosuppressant therapy. Notably, patients with MN demonstrate a higher overall response rate and superior treatment outcomes compared to those with TMA.